The Effect Of Influencers And Brand Image On Impulse Buying Among Economics Education Students At STKIP Majenang (International Journal of Economics Management and Social Science, 2026)
This study aims to analyze the influence of influencers and brand image on impulse buying behavior, particularly among students of the Economic Education program at STKIP Majenang, Class of 2020-2022. The study employs a quantitative method with a survey approach, using a questionnaire as the data collection tool. The sample consists of 39 students selected through purposive sampling. The results show that the influencer variable has a positive and significant impact on impulse buying with a significance value of 0.001 < 0.05, while brand image does not have a significant partial effect (significance value of 0.327 > 0.05). However, when both variables are tested simultaneously, it is found that influencer and brand image together have a significant impact on impulse buying with a significance value of 0.003 < 0.05. These findings suggest that influencers, as a marketing element on social media, play a crucial role in driving impulse buying behavior, while brand image strengthens this effect. This research provides insights for companies to optimize marketing strategies by integrating influencer marketing and strengthening brand image to boost impulse buying sales on e-commerce platforms. Keywords: influencer, brand image, impulse buying, students